Demographic Analysis of Undergrowth Vegetation under Populus tremuloides Michx., Forests in North America - Bahar, N. (Indian Forester, 2001)
The present paper deals with the demographic analysis of undergrowth under Populus tremuloides Michx. Forest at Site I (Utah), Site II (Idaho) and Site III (South Dakota) in North America. 51 plant species were recorded from three sites. Total number of plant species was recorded 27, 18 and 15 at Site I, Site II and Site III respectively. Maximum number of Shrubs (10) were recorded at Site I (Utah) and minimum number (2) was recorded at Site II (Idaho). The highest IVI recorded was of Berberis repens (30.87), Symphoricarpos oreophilus (69.77) and Amelanchier alnifolia (49.53) shrubs at Site I, Site II and Site III respectively. Higher stand density enables light, radiation and rain to reach ground floor, which affects demography of the undergrowth.